Blendeed learning & MOOC - Soares, Filomena Baptista (2017)
The word MOOC (Massive Open Online Courses) has its origins in an experience carried out by George Siemens and Stephen Downes in 2008 based on the theory of connectivism and social constructivism. This worldwide phenomenon appeared as an evolution of the Open Educational Resources (OER) movement. They are a new style of online classes that allow any person with web access, anywhere, usually free of charge, to participate through video lectures, computer graded tests and discussion forums which have been taking the attention of many higher education institutions around the world. The purpose of this paper is to give us an overview of how MOOCs and Blended Learning can be used with as an educational strategy in a Mathematics Course of “non Mathematic” degree programs. The pedagogical strategy embraced in this venture, was to combine the potentialities of some, already available, “good” OER, with a blended working scheme established side by side with the course development, regarding fundamental issues considered as prerequisites to it. We will explain the specific contents involved, as well as the general and specific objectives and outcomes, the evaluation procedures established for the course support and development, finishing with a summary of the complete results. We did not want to discover the “wheel”, it is from common knowledge for decades, but to present alternative ways to make a good use of it.